Fermentation of the Brown Seaweed Alaria esculenta by a Lactic Acid Bacteria Consortium Able to Utilize Mannitol and Laminari-Oligosaccharides - Leila Allahgholi; Madeleine Jönsson; Monica Daugbjerg Christensen; Andrius Jasilionis; Mehrnaz Nouri; Shahram Lavasani; Javier A. Linares-Pastén; Guðmundur Óli Hreggviðsson; Eva Nordberg Karlsson (Fermentation, 2023)
The brown seaweed Alaria esculenta is the second most cultivated species in Europe, and it is therefore of interest to expand its application by developing food products. In this study, a lactic acid bacteria consortium (LAB consortium) consisting of three Lactiplantibacillus plantarum strains (relative abundance ~94%) and a minor amount of a Levilactobacillus brevis strain (relative abundance ~6%) was investigated for its ability to ferment carbohydrates available in brown seaweed. The consortium demonstrated the ability to ferment glucose, mannitol, galactose, mannose, and xylose, of which glucose and mannitol were the most favored substrates. No growth was observed on fucose, mannuronic and guluronic acid. The consortium used different pathways for carbohydrate utilization and produced lactic acid as the main metabolite. In glucose fermentation, only lactic acid was produced, but using mannitol as a carbohydrate source resulted in the co-production of lactic acid, ethanol, and succinate. Xylose fermentation resulted in acetate production. The consortium was also able to utilize laminari-oligosaccharides (DP2-4), obtained after enzymatic hydrolysis of laminarin, and produced lactic acid as a metabolite. The consortium could grow directly on A. esculenta, resulting in a pH decrease to 3.8 after 7 days of fermentation. Incubation of the same seaweed in corresponding conditions without inoculation resulted in spoilage of the seaweed by endogenous bacteria.